(untitled) (Revista Ciência Agronômica, 2017)
One of the alternatives for achieving sustainable agriculture and a reduction in production costs, especially with phosphate fertilisers, is to inoculate seeds with bacteria of the genus Azospirillum. The aim of this study therefore, was to evaluate residual phosphate fertilisation and Azospirillum brasilense, together with the contribution of straw from maize intercropped with Marandu grass, on leaf nutritional content, yield components and winter bean yield. The experiment was carried out on the Teaching and Research Farm, of the School of Engineering at UNESP, located in Selvíria in the State of Mato Grosso do Sul, in a typic clayey dystrophic Red Latosol. The experimental design was of randomised blocks with four replications in a 5 x 2 factorial scheme. The treatments consisted of beans sown on straw from maize intercropped with Marandu grass on areas that had received five levels of P2O5 in the form of MAP, applied during an initial cultivation of black oats (0, 30, 60, 120 and 240 kg ha-1), both with and without inoculation of the oat and maize which preceded the beans with Azospirillum brasilense. Leaf nutrient content, leaf chlorophyll index (ICF), yield components and bean productivity were all evaluated. Inoculation with Azospirillum brasilense of the black oat and maize seeds improved the nutritional status of the plants, but had a negative effect on grain yield. Fertilisation of the oat crop with phosphorus had a positive residual effect on the beans, with increases in yield components and grain yield.